2021
DOI: 10.5194/essd-13-3439-2021
|View full text |Cite
|
Sign up to set email alerts
|

The NY-Ålesund TurbulencE Fiber Optic eXperiment (NYTEFOX): investigating the Arctic boundary layer, Svalbard

Abstract: Abstract. The NY-Ålesund TurbulencE Fiber Optic eXperiment (NYTEFOX) was a field experiment at the Ny-Ålesund Arctic site (78.9∘ N, 11.9∘ E) and yielded a unique meteorological data set. These data describe the distribution of heat, airflows, and exchange in the Arctic boundary layer for a period of 14 d from 26 February to 10 March 2020. NYTEFOX is the first field experiment to investigate the heterogeneity of airflow and its transport of temperature, wind, and kinetic energy in the Arctic environment using t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…The simulated height of the model revealed only altitudes of 20-50 m [13], while the measurement campaign by Vihma et al [30] with tethered balloons reveals long jets at a mean height of h = 514 m, a mean velocity of v = 6.5 m s and wind direction of SE, which were caused by katabatic flows from the nearby glacier Brøggerbreen [30]. In the ABL experiment NYTEFOX by Zeller et al [47] a typical speed of katabatic winds was observed with up to v ≤ 5 m s in parallel with clear sky conditions and a weak synoptic wind. In these conditions small-scale effects dominate the local ABL.…”
Section: Discussionmentioning
confidence: 95%
“…The simulated height of the model revealed only altitudes of 20-50 m [13], while the measurement campaign by Vihma et al [30] with tethered balloons reveals long jets at a mean height of h = 514 m, a mean velocity of v = 6.5 m s and wind direction of SE, which were caused by katabatic flows from the nearby glacier Brøggerbreen [30]. In the ABL experiment NYTEFOX by Zeller et al [47] a typical speed of katabatic winds was observed with up to v ≤ 5 m s in parallel with clear sky conditions and a weak synoptic wind. In these conditions small-scale effects dominate the local ABL.…”
Section: Discussionmentioning
confidence: 95%
“…The SoPhaBs described here have an improved design compared to an earlier type described in Lapo et al [17] and Zeller et al [18], particularly with respect to the thermoelectric control, carrying case, and handling and routing of the fiber-optic cables.…”
Section: Methodsmentioning
confidence: 93%
“…This enables measurements of the small-scale and rapidly changing gradients and individual turbulent eddies. By installing the cable in different configurations such as coils (Sigmund et al 2017;Zeller et al 2021), or arrays (Thomas et al 2012), sharp temperature gradients near the surface can be measured. Here, we apply a harp-shaped DTS set-up to measure the temperature profile over and within the grass with 2 cm resolution.…”
Section: Alternative Approach: Surface Length Scale For Short Canopiesmentioning
confidence: 99%